(untitled) (World Science, 2020)
The prevalence of diabetes mellitus (DM) in the world in general, and in Ukraine in particular, is increasingly showing signs of an epidemic. This chronic disease contributes significantly to increased spending on health care services due to severe complications, loss of capacity to work and increased mortality. Medical specialists see a way out of the crisis as providing patients with the opportunity to manage their disease on their own — in partnership with pharmaceutical specialists, namely, clinical care providers. Traditionally, the role of the pharmacist has been focused on delivering medicines and advising patients on medication, but recently, pharmaceutical professionals have started to become more involved in the management system of type I and type II DM by providing pharmaceutical care (PhС) to patients, thus optimizing treatment, improving clinical outcomes and reducing costs.